Implementing the Green Economy - Kern, Florian (Ökologisches Wirtschaften - Fachzeitschrift, 2013)
The economic crisis has given new impetus to discussions about green growth and the green economy. But how can the concept of a green economy be translated into concrete action? The field of energy production and consumption provides examples of deliberate transition management.